Prosthetic shape, but not stiffness or height, affects the maximum speed of sprinters with bilateral transtibial amputations - Taboga, P.; Beck, O. N.; Grabowski, A. M. (PLOS ONE, 2020)
Running-specific prostheses (RSPs) have facilitated an athlete with bilateral transtibial amputations to compete in the Olympic Games. However, the performance effects of using RSPs compared to biological legs remains controversial. Further, the use of different prosthetic configurations such as shape, stiffness, and height likely influence performance. We determined the effects of using 15 different RSP configurations on the maximum speed of five male athletes with bilateral transtibial amputations. These athletes performed sets of running trials up to maximum speed using three different RSP models (Freedom Innovations Catapult FX6, Össur Flex-Foot Cheetah Xtend and Ottobock 1E90 Sprinter) each with five combinations of stiffness category and height. We measured ground reaction forces during each maximum speed trial to determine the biomechanical parameters associated with different RSP configurations and maximum sprinting speeds. Use of the J-shaped Cheetah Xtend and 1E90 Sprinter RSPs resulted in 8.3% and 8.0% (p<0.001) faster maximum speeds compared to the use of the C-shaped Catapult FX6 RSPs, respectively. Neither RSP stiffness expressed as a category (p = 0.836) nor as kN·m-1 (p = 0.916) affected maximum speed. Further, prosthetic height had no effect on maximum speed (p = 0.762). Faster maximum speeds were associated with reduced ground contact time, aerial time, and overall leg stiffness, as well as with greater stance-average vertical ground reaction force, contact length, and vertical stiffness (p = 0.015 for aerial time, p<0.001 for all other variables). RSP shape, but not stiffness or height, influences the maximum speed of athletes with bilateral transtibial amputations.